A Review on the Strength of Fishing Net; The Effect of Material, Yarn Diameter and Mesh Size - SHARIF, NUR FARAH HANIS; KUNCHI MON , SITI ZAHARAH (Progress in Engineering Application and Technology, 2021)
Fishing net can be varies in netting material, yarn diameter and mesh size. The main objective of this research is to review the strength of fishing net that produced from different materials and the effect of different yarn diameter and mesh size on the mechanical performance of the fishing net Different materials, yarn diameters and mesh size can influence the performance of the fishing net. PA material tends to have the highest tensile strength properties compared to PP and PE material. The increase of yarn diameter can have higher tensile strength, higher breaking load and the elongation at break to the fishing net. The higher the mesh size of the fishing net could give a good drag coefficient, higher bending stiffness and higher breaking strength. Furthermore, based on the review from previous studies, the best solution is recommended to the netting material, yarn diameter and the mesh size of the fishing net.